Hand Hygiene Awareness, Attitude and Compliance among House Officers in Public-Sector Dental Institutes- A Questionnaire-Based Study - Hammad Hassan, Saira Khalid, Aamir Rafique, Farwa Zahid, Maleeha Khurram, Ramsha Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objectives of this study were to evaluate the compliance of hand hygiene among dental health care professionals, to access different variables associated with hand hygiene and to identify possible ways of improving hand hygiene compliance. Methods: This descriptive cross-sectional study was done to access the hand hygiene compliance, knowledge and practice of dental house officers in public dental institutes using a questionnaire developed by the authors. Descriptive statistics and chi square test were performed and a P value <0.05 was taken as significant. Results: 88 dental house officers working in different clinical departments participated in this study. 90% of the respondents believed that hand hygiene plays an important role in cross infection control. More than two-third were aware of all the steps recommended for hand washing, but more than half were not following them. 60% of the respondents wash their hands before and after touching each patient. However, 30% wash hands after each patient and 10% only wash hands before touching every patient. Fifty-five (55.8%) of the participants routinely use alcohol-based rub for hand hygiene. There was a significant difference regarding hand hygiene training among different departments. (p<0.001) Majority of house officers working in prosthodontics and surgery had not received hand hygiene training. Conclusion: Hand hygiene compliance is found to be acceptable when compared with developing countries. However, there was lack in knowledge. Dental graduates should be made aware of CDC and ADA guidelines. Better facilities and instruction for dental students should be encouraged. Hand hygiene quality needs to be improved on an urgent basis.